Association between the functional PTPN22 G788A (R263Q) polymorphism and susceptibility to autoimmune diseases: A meta-analysis - Bae, Sang-Cheol; Lee, Young Ho (Cellular and Molecular Biology, 2018)
This study explored whether the functional protein tyrosine phosphatase nonreceptor 22 (PTPN22) G788A (R263Q) polymorphism is associated with susceptibility to autoimmune diseases. A meta-analysis was conducted using 23 comparative studies with a total of 16,719 patients and 17,783 controls. The meta-analysis showed an association between the A allele of the PTPN22 G788A polymorphism and decreased risk of autoimmune diseases in all subjects (p < 0.001). Analysis after stratification by ethnicity indicated that the PTPN22 788A allele was significantly associated with autoimmune diseases in Europeans (p < 0.001) but not in Latin Americans. Meta-analysis by autoimmune disease type showed a significant negative association between the PTPN22 788A allele and systemic lupus erythematous (SLE) (p = 001), rheumatoid arthritis (RA) (p = 0.008), ulcerative colitis (UC) (p = 0.016), but not Crohn's disease (CD). A single study for each showed no association between the PTPN22 788A allele and systemic sclerosis, giant cell arteritis, Henoch-schonlein purpura, uveitis, and Grave's disease. This meta-analysis demonstrates that the PTPN22 G788A polymorphism confers protection against SLE, RA, and UC, supporting evidence of association of the PTPN22 gene with a subgroup of autoimmune diseases.